Zero in the brain: A voxel-based lesion–symptom mapping study in right hemisphere damaged patients. (April 2016) - Benavides-Varela, Silvia; Passarini, Laura; Butterworth, Brian; Rolma, Giuseppe; Burgio, Francesca; Pitteri, Marco; Meneghello, Francesca; Shallice, Tim; Semenza, Carlo
Abstract: Transcoding numerals containing zero is more problematic than transcoding numbers formed by non- zero digits. However, it is currently unknown whether this is due to zeros requiring brain areas other than those traditionally associated with number representation. Here we hypothesize that transcoding zeros entails visuo-spatial and integrative processes typically associated with the right hemisphere. The investigation involved 22 right-brain-damaged patients and 20 healthy controls who completed tests of reading and writing Arabic numbers. As expected, the most significant deficit among patients involved a failure to cope with zeros . Moreover, a voxel-based lesion–symptom mapping (VLSM) analysis showed that the most common zero -errors were maximally associated to the right insula which was previously related to sensorimotor integration, attention, and response selection, yet for the first time linked to transcoding processes. Error categories involving other digits corresponded to the so-called Neglect errors, which however, constituted only about 10% of the total reading and 3% of the writing mistakes made by the patients. We argue that damage to the right hemisphere impairs the mechanism of parsing, and the ability to set-up empty-slot structures required for processing zeros in complex numbers; moreover, we suggest that the brain areas located in proximity to the right insula play a role in the integration of the information resulting from the temporary application of transcoding procedures.